Enhancement Technology for Electrospray Polyvinyl Alcohol (PVA) Nano?ber from Zuheros Nano: A Preliminary Study - Mostapha, Marhaini; Gunawan, Win Indra; Sutriyono; Widayanti; Yuniati, Anis (Proceeding International Conference on Science and Engineering, 2020)
Polyvinyl alcohol PVA nanofiber is a biocompatible material that has numerous potential in health application include as bone and tissue implant, anti-fungal, anti-microbial, air filter and waste water treatment. In this study, the electrospin fiber has successfully fabricated byusing Zuheros Nano-electrospin machine. This is a new generation of electrospin machine which offer a faster, safer, controlled spinning conditions and highly reproducible. The 6 and 8 wt % of PVA was prepare and operated at different electric field of 15 and 20 kV at different distance between tip to collector (TDC) of 15 and 17cm.The physical characteristics of electrospin fiber were observed under optical microscope. Result shows that at higher voltage 20 kV, TDC 17 cm of 8 wt % PVA has produce a smooth, fine and well arrange of fibers formation compared to other electrospin parameter. The PVA electrospin membrane was successfully formed as spray durations increased to 90 minutes. The different polymer concentration (wt%), TDC (cm) and electrospray voltage (kV) effects the PVA nano-fiber formation.